Penegakan Hukum Terhadap Kebakaran Hutan Di Kabupaten Pelalawan Provinsi Riau Berdasarkan Undang-Undang Nomor 41 Tahun 1999 Tentang Kehutanan - Andrew Shandy Utama; Rizana Rizana (Jurnal Selat, 2020)
Forest fires are not a rare phenomenon in Indonesia, especially in Pelalawan Regency, Riau Province. In 2019 there was a forest fire in Pelalawan Regency covering an area of ​​827 Ha and was directly visited by President Joko Widodo on September 17, 2019. This study aims to explain law enforcement against forest fires in Pelalawan Regency, Riau Province based on Law Number 41 of 1999 concerning Forestry . The method used in this research is sociological law research. Based on Article 50 paragraph (3) letter d of Law Number 41 Year 1999 concerning Forestry, it is stated that everyone is prohibited from burning forests. However, in 2019 there were forest fires in Pelalawan District covering an area of ​​827 hectares. The implementation of Law No. 41/1999 on Forestry against forest fires in Pelalawan District has not gone as expected. Burning forests is a criminal act. Law enforcement against the crime of forest burning in Pelalawan Regency, namely based on Article 78 paragraph (3) of Law Number 41 of 1999 concerning Forestry, it is stated that anyone who deliberately burns forests can be punished with imprisonment of up to 15 years and a maximum fine. IDR 5,000,000,000. The Pelalawan Regency Government can take preventive measures to minimize the occurrence of forest fires by carrying out legal counseling to the community regarding the prohibition of burning forests and increasing the role of the community in preserving the surrounding forests.